Pengaruh Penggunaan Media Augmented Reality Terhadap Hasil Belajar Siswa Kelas VIII Mata Pelajaran Ilmu Pengetahuan Alam di SMPN 3 Kinali - Lbs, Intan Nur Fatihah; Darmansyah, Darmansyah; Anugrah, Septriyan; Rahmayanti, Elsa (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The lack of creativity of educators in the use of media during the learning process is one of the driving factors for the low learning outcomes of grade VIII students in Natural Sciences (IPA) at SMP N 3 Kinali. This study aims to determine the Effect of the Use of Augmented Reality (AR) Media on the Learning Outcomes of Grade VIII Students in Natural Sciences (IPA) at SMP 3 KINALI. The type of research used is a quantitative approach with a quasi-experimental method consisting of an experimental class (VIII.4) and a control class VIII (3). The sampling technique in this study is purposive sampling. The research design used is the Nonequivalent Control Group. Based on the results of data analysis, it can be concluded that the use of AR media has a significant positive influence on the improvement of learning outcomes of grade VIII students in science subjects at SMP 3 Kinali. The average learning outcomes of students in the experimental class using AR media were significantly higher than in the control class. This indicates that AR media can be an effective alternative to increase students' motivation to learn and facilitate better understanding of concepts